Effect Of Mandibular Reconstruction With Titanium Plate In Squamous Cell Carcinoma - Asaduzzaman , Ashik Abdullah Imon, Md. Wares Uddin, Wahidujjaman4, Ruman Banik, Mahmudul Hasan, Mohidul Islam, Tamanna Khandker Tonny, Md. (South Eastern European Journal of Public Health, 2025)
Background: Oral squamous cell carcinoma (OSCC) frequently necessitates mandibular resection, posing significant challenges for functional and aesthetic reconstruction. Titanium plates are increasingly utilized in resource-limited settings due to their accessibility, strength, and biocompatibility. Aim of the study: This study aimed to evaluate the clinical outcomes of mandibular reconstruction using titanium plates in OSCC patients, focusing on operative time, post-operative healing, and long-term stability. Methods: A prospective clinical study was conducted on 40 OSCC patients undergoing mandibular resection and reconstruction with titanium plates at Bangabandhu Sheikh Mujib Medical University. Data on demographics, operative time, post-operative complications, and long-term outcomes were collected and analyzed using SPSS v26.0. Result: The cohort had a mean age of 56.3 ± 12.3 years, with 68% male predominance. The average operative time was 5.87 ± 0.63 hours. Post-operative complications included infection (7.5%), hematoma (5%), plate fracture (2.5%), and implant failure (2.5%), while 82.5% of patients exhibited no complications. Long-term issues included joint stiffness (12.5%) and chronic pain (10%), with 75% of patients showing no abnormalities. Conclusion: Titanium plate-based mandibular reconstruction in OSCC patients demonstrated favorable outcomes with minimal complications, offering a viable alternative in settings where microvascular free flaps are not feasible.